Forming technique of ski sport of students of the first course of sporting institute of higher education - Sidorova T.V (Kharkov National Pedagogical University, 2010)
Is certain the most rational method of the speed-up teaching of students of the first course of discipline «Ski sport». Positions are taken into account to credit-module departmental teaching. The individual differentiated technology of the accelerated training to ways of movement on a ski is proved. Technology includes three methods of teaching. Application of methods is varied depending on sporting specialization of students and development of their physical qualities. The rational parity of employment on training to technics of classical and skating styles of movement on a ski is determined.